(3GdeYQGL aj TQM GdefgGLs - (3YR GdOjf Hf GdMSf Hf Ydj GdeDjO , GdgGOi Edi GdMbs; (3jMji Hf GdMSf GdbQTj,J (B862 (3g` s
(3ChdgG (B:s
(3Gdbhd ai GdESJWGYI EYde Cf gPG GdHGH ehVYg Yde dCfg ai PcQ eYfi fhY ef hgh GdbOQI hPcQ HYV CMcGegG , dcf deG cGf GdcdGe ajg jHfi Ydjg UMI ePgH GdYOdjI haSGO ePgH GdLHQjI s
(3BNQgG (B:s
(3hCLhO eG jYJeO Ydjg ef GdCOdi ggfG ELeGY GdYJQI ai GdReGf GdChd Ydi LhGRgG ajge hYOe LhGRgG ai ZjQge bHd MOhK ePgH GdEeGejI hGddg hdi GdJhajb s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdahGJM HGdSejcs
(3Ydi WQJgG JedcGJs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdESdGejs